The effect of single nucleotide polymorphisms on depression in combination with coronary diseases: a systematic review and meta-analysis - Zhang, Jing; Gao, Lu; Yang, Guan Lin; Kong, De Zhao (Frontiers in Endocrinology, 2024)
No